Changes in the repertoire of bovine milk proteins during mammary involution - Irina Boggs; Brad Hine; Grant Smolenski; Kasper Hettinga; Lina Zhang; Thomas T. Wheeler (EuPA Open Proteomics, 2015)
Changes of abundance that occur in the repertoire of low abundance milk proteins after cessation of milk removal have not been characterised. Skimmed milk and whey from cows sampled at day 0 and either day 3 or day 8 after drying off were subjected to three untargeted proteomics techniques; 2-D gel electrophoresis, GeLC-MS, and dimethyl isotopic labelling of tryptic peptides. The changes observed included 45 fragments of abundant milk proteins and 36 host-defence proteins, suggesting activation of proteolysis and inflammation. The findings form a basis for adding value to dairy production. Keywords: Host defence, Dairy, Drying off, Immune response